2003
DOI: 10.1002/pen.10131
|View full text |Cite
|
Sign up to set email alerts
|

Blends of nylon/acrylonitrile butadiene rubber: Effects of blend ratio, dynamic vulcanization and reactive compatibilization on rheology and extrudate morphology

Abstract: The melt flow behavior of thermoplastic elastomers from nylon and nitrile rubber (NBR) was studied as a function of blend ratio, dynamic crosslinking, compatibilization and temperature. The morphology of the extrudates, i.e., the size, shape and distribution of the domains, was analyzed. Uncompatibilized and compatibilized blends showed pseudoplastic behavior. The viscosity of the blends showed positive deviation from a linear rule of mixtures. Compatibilization using chlorinated polyethylene (CPE) increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
1
30
0
1
Order By: Relevance
“…Some studies on blending of NBR to improve impact strength and toughness were reported; with PVC, [17] PP, [18] and polyamide. [19][20][21] As noted above, many studies have reported blending PBS with various thermoplastic polymers. To best of our knowledge, no work has been published with respect to blending PBS with elastomer.…”
Section: Introductionmentioning
confidence: 96%
“…Some studies on blending of NBR to improve impact strength and toughness were reported; with PVC, [17] PP, [18] and polyamide. [19][20][21] As noted above, many studies have reported blending PBS with various thermoplastic polymers. To best of our knowledge, no work has been published with respect to blending PBS with elastomer.…”
Section: Introductionmentioning
confidence: 96%
“…Extensive research work related to mechanical and morphological behaviour of nylon/elastomer blends have been reported [8][9][10]. To our knowledge, there has been very little study on rheological properties of these blends [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…A partir de 2000 destacam-se: Mehrabzadeh e Delfan [17] apresentando TPVs PA-6/NBR (40/60) utilizando diferentes reticulantes como: enxofre, peróxido de dicumila e resina fenólica, obtendo melhor desempenho em termos de inchamento em óleo e propriedades mecânicas para o sistema baseado em resina fenólica. Kumar et al [18] estudaram o comportamento de fluxo de TPVs a base de PA (6/6-6) e NBR para diferentes proporções de PA/NBR (70/30, 50/50, 30/70) reticulados com peróxido de dicumila com e sem o uso de polietileno clorado, como agente compatibilizante, obtendo TPVs com domínios elastoméricos muito uniformes. Chowdhury et al [19,20] , descrevem TPVs de PA/ NBR a partir de um terpolímero de poliamida (6, 6-6, 6-10) e uma NBR carboxilada reticulada com enxofre e aceleradores, obtendo um material com boa resistência em óleo e morfologia com aspecto homogêneo, principalmente para a composição 40/60 de PA/NBR.…”
Section: Methodsunclassified